2018
DOI: 10.1080/03602532.2018.1428616
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of the cannabinoid-related orphan receptors GPR3, GPR6, and GPR12

Abstract: GPR3, GPR6 and GPR12 are three orphan receptors that belong to the Class A family of G protein-coupled receptors (GPCRs). These GPCRs share over 60% of sequence similarity among them. Because of their close phylogenetic relationship GPR3, GPR6 and GPR12 share a high percentage of homology with other lipid receptors such as the lysophospholipid and the cannabinoid receptors. On the basis of sequence similarities at key structural motifs, these orphan receptors have been related to the cannabinoid family. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 115 publications
(217 reference statements)
0
47
1
3
Order By: Relevance
“…The CB1 receptor has been found in the central and peripheral nervous system, lungs, kidneys, and liver; the CB2 receptor is expressed by immune and hematopoietic cells. Recent evidence points out that endocannabinoids interact with not only these receptors but also G protein-coupled receptor 55 (GPR55) and all PPAR isoforms [96,132,133]. For example, it has been shown that endocannabinoids can serve as double agonists of PPARγ and CB2 and neutralize chronic inflammation [95].…”
Section: Ppar Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The CB1 receptor has been found in the central and peripheral nervous system, lungs, kidneys, and liver; the CB2 receptor is expressed by immune and hematopoietic cells. Recent evidence points out that endocannabinoids interact with not only these receptors but also G protein-coupled receptor 55 (GPR55) and all PPAR isoforms [96,132,133]. For example, it has been shown that endocannabinoids can serve as double agonists of PPARγ and CB2 and neutralize chronic inflammation [95].…”
Section: Ppar Researchmentioning
confidence: 99%
“…Endocannabinoid receptors, like PPARs, are expressed by alveolar macrophages, eosinophils, monocytes, and dendritic cells [42,135]. The receptors PPARα, CB1, and CB2 that directly interact with endocannabinoids [132] are located in the bronchi of mice [136]. The endocannabinoid 2-AG and its receptor CB2 play an important role in the inhibition of mast cells (MC), as well as in the migration of eosinophils to the respiratory tract [137].…”
Section: Rvd1mentioning
confidence: 99%
“…The hGPR6 homology model was constructed based upon the X-ray crystal structure of the Sphingosine-1-phosphate receptor 1 (S1P1) at a 2.8 Å resolution [PDB identifier: 3V2Y] [28]. S1P1 shares 33% sequence homology (similarity) with GPR6 sequence [14]. Both share essential features such as (1) the absence of helix kinking proline residues in TMH2 (2.58 or 2.59) and TMH5 (5.50), (2) the presence of an acidic residue E1.49 before the highly conserved N1.50 in TMH1 and (3) the presence of an internal disulfide bridge in the EC2 loop (see Supplementary Materials, Figure S1 for Human sequence alignments of S1P1 and GPR6 receptors).…”
Section: Gpr6 Inactive-state Model Developmentmentioning
confidence: 99%
“…While the G-protein independent signaling pathway via β-arrestin requires TMH7 movement to expose the extreme end of the C-terminus for the β-arrestin to couple with it [46]. GPR6 has been shown to signal via G-protein and to have high constitutive activity [14]. Activation via G-protein occurs upon changes in intrahelical interactions between TMH3 and TMH6 [47].…”
Section: Ionic Lock and Toggle Switchmentioning
confidence: 99%
See 1 more Smart Citation